Educational quality of public health programs at a university in the Northeast - Chanthakhuembong, Kamolporn (UBRU Journal for Public Health Research, 2023)
The purpose of this research were to study the results of educational management in public health science curriculum. Analyzing data from the educational quality assurance report, educational service system, then present the analysis results in descriptive statistics and give a summary of the research results. The results of data analysis found that 1) The number of courses offered at the bachelor’s level in the academic year 2014-2021 is 4 courses. 2) Educational Quality Assurance Assessment Results found that it was at a good level for 6 academic years, namely 2015, 2017-2021 and 2016 are at fair level. 3) The ratio of students to FTES instructors found that in the academic year 2014-2021, the FTES was higher than the criteria, with the highest FTES in the year 2021 (63.50:1), followed by the year 2020 (49.13:1) and the lowest in 2019 (23.97:1) 4) The number of students admitted more than the plan for the academic year 2014 increased by 248.33%, followed by Academic year 2015, 358.33% and Academic year 2019, the lowest, 134.84% 5) The retention rate of students found that the 2018 academic year had the highest retention rate of 84.52%, followed by the 2014 academic year with the retention rate of 82.56% and the 2021 academic year had the lowest number of students at 43.40%. 6) Employment conditions: Employment of graduates within 1 year 2014-2021, most of them are employed at more than 80%. In summary, the educational management results are important information and useful for formulating educational management guidelines and urgent development plans in terms of the ratio of full-time instructors to students, number of students admitted.